1993
DOI: 10.1002/hep.1840170629
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration and chimerism after whole-organ transplantation: The basis of graft acceptance

Abstract: Improvements in the prevention or control of rejection of the kidney and liver have been largely interchangeable (1,2) and then applicable, with very little modification, to thoracic and other organs. However, the mechanism by which anti rejection treatment permits any of these grafts to be "accepted" has been an immunological enigma (3,4). We have proposed recently that the exchange of migratory leukocytes between the transplant and the recipient with consequent long-term cellular chimerism in both is the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
287
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 711 publications
(296 citation statements)
references
References 109 publications
8
287
0
1
Order By: Relevance
“…Solid organ transplants may also benefit from microchimerism detection, as demonstrated by some authors who have shown that the presence of donor circulating cells after transplantation is directly correlated to a significantly lower incidence of acute rejection (14)(15)(16)(17) or even leads to tolerance (18). Many studies based on microchimerism detection after solid organ transplantation have been published.…”
Section: Introductionmentioning
confidence: 95%
“…Solid organ transplants may also benefit from microchimerism detection, as demonstrated by some authors who have shown that the presence of donor circulating cells after transplantation is directly correlated to a significantly lower incidence of acute rejection (14)(15)(16)(17) or even leads to tolerance (18). Many studies based on microchimerism detection after solid organ transplantation have been published.…”
Section: Introductionmentioning
confidence: 95%
“…However, it has become clear that caution must be exercised in interpret ing the results of studies based on tumor xenografts in which the vascular supply of a tumor plays a pivotal role [1], Similar to the situation in human allografts [2], xeno transplantation of vascularized tissues is followed by KARGER.…”
Section: Introductionmentioning
confidence: 99%
“…Although Starzl and colleagues made this observation 20 years ago, the significance of this "microchimerism" [23] remains enigmatic. Starzl hypothesized that microchimerism is the result of donor T cells depleting graft-specific host T cells and donor cells eliminating graft-specific effector T cells, and that microchimerism is achieved when a balance of graft versus host and host versus graft immune responses is reached [27]. One of the major criticisms of this model is that it is still unclear whether microchimerism is the cause or result of tolerance.…”
Section: Mechanisms Of Spontaneous Liver Allograft Acceptancementioning
confidence: 97%